SOCIAL AND ECONOMIC INEQUALITY IN A GLOBAL PERSPECTIVE: A LITERATURE REVIEW OF POLICIES AND INTERVENTIONS - Loso Judijanto; Al-Amin (Adisam Publisher, 2025)
Social and economic inequality is a global issue that has a significant impact on many aspects of life, including health, education and economic stability. This research aims to review the literature on policies and interventions implemented around the world to address this inequality. The literature review shows that inequality is often caused by unfair economic policies, unequal income distribution, and limited access to fundamental services such as education and health. In addition, neoliberal policies and the effects of globalisation have exacerbated economic inequality between developed and developing countries. Various strategies have been implemented to reduce inequality, such as income redistribution through progressive taxation, social assistance programmes, and improved access to education and health services. The findings of this study emphasise the importance of a multidimensional approach and cross-sectoral cooperation in designing and implementing effective policies to reduce social and economic inequality globally.